2022
DOI: 10.3390/cancers14163980
|View full text |Cite
|
Sign up to set email alerts
|

Super Enhancer-Regulated LINC00094 (SERLOC) Upregulates the Expression of MMP-1 and MMP-13 and Promotes Invasion of Cutaneous Squamous Cell Carcinoma

Abstract: Long non-coding RNAs (lncRNAs) have emerged as important regulators of cancer progression. Super enhancers (SE) play a role in tumorigenesis and regulate the expression of specific lncRNAs. We examined the role of BRD3OS, also named LINC00094, in cutaneous squamous cell carcinoma (cSCC). Elevated BRD3OS (LINC00094) expression was detected in cSCC cells, and expression was downregulated by SE inhibitors THZ1 and JQ1 and via the MEK1/ERK1/2 pathway. Increased expression of BRD3OS (LINC00094) was noted in tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recent studies have revealed several lncRNAs, such as MALAT1, PVT1, LINC00319 , involved in the progression of cSCC (20,21,54,55). Additionally, our previous studies have revealed the role of lncRNAs PICSAR, PRECSIT and SERLOC in cSCC (16-19).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent studies have revealed several lncRNAs, such as MALAT1, PVT1, LINC00319 , involved in the progression of cSCC (20,21,54,55). Additionally, our previous studies have revealed the role of lncRNAs PICSAR, PRECSIT and SERLOC in cSCC (16-19).…”
Section: Discussionmentioning
confidence: 90%
“…LncRNAs have been studied in cSCC but their role in cSCC progression is largely unknown (15). We have previously characterized and named three lncRNAs that are upregulated in cSCC and regulate progression of cSCC via different mechanisms, namely PICSAR (p38 inhibited cutaneous squamous cell carcinoma-associated lincRNA) (16,17), PRECSIT (p53 regulated carcinoma-associated STAT3-activating long intergenic non-protein coding transcript) (18) and SERLOC (super enhancer and ERK1/2-regulated long Intergenic non-protein coding transcript overexpressed in carcinomas) (19). Additionally, PVT1 was discovered as a lncRNA that promotes cSCC progression by suppressing cellular senescence by inhibiting CDKN1A expression and preventing cell cycle arrest (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Superenhancers play a role in tumorigenesis and regulate the expression of speci c lncRNAs. Piipponen et al [35] discovered that superenhancer-regulated LINC00094 upregulated the expressions of matrix metalloproteinase (MMP)-1 and MMP-13 and promoted the invasion of cutaneous SCC cells. That study also reported upregulated LINC00094 expression in cutaneous SCC cells and the downregulation of LINC00094 expression by SE inhibitors THZ1 and JQ1 through the MEK1/ERK1/2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the abundant highly organized collagenous ECM produced by these cells, being a major determinant of the biomechanical properties of the cornea ( Yang et al, 2022 ). Indeed, 13 of the 73 GTEx-nominated genes encode for core matrisome constituents ( COL6A2 , COL6A3 , and FBLN2 ), glycosylation and sulfation enzymes that are likely to affect proteoglycans and glycoproteins–rich ECM (keratan sulfotransferase CHST1 , ST6GALNAC1 , GLT8D2 , and GALNT6 ), an endoplasmic reticulum to Golgi export component ( SEC24D ) involved in procollagen trafficking ( Lu et al, 2022 ), a component of the sarcoglycan complex anchoring cells to the ECM ( SGCA ), and ECM remodeling actors and regulators ( LINC0094 , MXRA7 , THBS4 , and SFRP1 ) ( Subramanian and Schilling, 2014 ; Wang et al, 2020 ; Piipponen et al, 2022 ; Shen et al, 2023 ). An additional eGene, the zinc transporter encoding gene SLC39A13 , is mutated in spondylodysplastic Ehlers–Danlos syndrome (OMIM 612350), a rare syndrome with multi-tissues manifestations: skeletal dysplasia, blue sclera, muscular hypotonia, and ocular impairments that include myopia and keratoconus.…”
Section: Discussionmentioning
confidence: 99%